Local Irradiation Sensitized Tumors to Adoptive T Cell Therapy via Enhancing the Cross-Priming, Homing, and Cytotoxicity of Antigen-Specific CD8 T Cells - Lai, Jin-Zhi; Zhu, Yan-Yang; Ruan, Mei; Chen, Ling; Zhang, Qiu-Yu (Frontiers in Immunology, 2019)
The successful generation of T cell-mediated immunity for the treatment of cancer has been a major focal point of research. One of the critical strategies of cancer immunotherapy is to efficiently activate antigen-specific CD8 T cells in the immunosuppressive tumor environment. Here, we used transgenic OT-I/CD45.2/Rag-/- mice as a source of effector CD8 T cells to determine whether irradiation combined with adoptive T cell transfer therapy could improve T cell proliferation and effector function in murine tumor models. Local irradiation combined with adoptive T cell therapy showed a synergistic effect on tumor growth inhibition in mice. Mechanistically, irradiation increased the release of tumor-associated antigens, which facilitated cross-presentation of tumor-associated antigens by dendritic cells and the priming of antigen-specific T lymphocytes. Additionally, irradiation enhanced the homing of the antigen-specific T cells to tumor tissues via the increased release of CCL5, CXCL9 and CXCL11 from tumor cells. Moreover, irradiation enhanced the proliferation and effector function of both adoptively transferred T cells and endogenous antigen-specific T cells. Our findings provide evidence to support that local irradiation enhanced the therapeutic efficacy of adoptive T cell therapy for cancer, indicating that the combination of radiotherapy and adoptive T cell therapy may be a promising strategy for tumor treatment.